Up-down asymmetry in vertical vection. (December 2015) - Seya, Yasuhiro; Shinoda, Hiroyuki; Nakaura, Yoshiya
Highlights: Vection was larger for upward motion of a stimulus than for downward motion. Up-down asymmetry in vection appeared during the latter part of stimulus presentation. Up-down asymmetry in optokinetic nystagmus (OKN) was also observed. Mechanisms underlying vection and OKN are related to each other. Abstract: To investigate whether up-down asymmetry similar to that reported in vertical optokinetic nystagmus (OKN), that is, larger OKN responses for upward motion than for downward motion, would appear in vertical vection, we conducted three experiments. In all three experiments, participants viewed a vertically moving random-dot pattern. In Experiments 1 and 2, participants reported vection using a joystick. After each trial, they were also asked to rate the vection magnitude experienced during the stimulus presentation. In Experiment 3, eye movements and vection magnitude (rated after each trial) in response to the stimulus were measured. The results of Experiment 1 showed larger vection magnitude for the upward motion of the stimulus than for the downward motion of it. However, vection onset latency did not change much with stimulus motion direction. Experiment 2 revealed that the up-down asymmetry in vection manifested progressively during the latter part of the stimulus presentation period. Experiment 3 showed clear up-down asymmetry in both OKN and vection magnitude. These results not only indicate that up-down asymmetry similar to that reported in vertical OKN appears in vertical vection, but they also support the notion that the mechanisms underlying vection and OKN are closely related to each other.